The difference between Skimming and Scanning in Indonesian Language Article Speed Reading Activities - Dewirsyah, Amnur Rivai; Rahayu, Enny (Jurnal Riset Ilmu Pendidikan, 2023)
This article is a literature review (library research) with the main study confirming the importance of scanning and skimming speed-reading strategies which aim to improve the quality of speed-reading activities carried out by each individual in finding main information from an article or writing that is relatively long but the time to read it is relatively narrow. With this article, it is hoped that each individual will be more active, initiative and creative in developing ideas in learning to increase willingness and apply techniques skimming and scanning in speed reading. Especially now that there is more and more knowledge contained in reading media in the form of online and online media. With this much knowledge, individuals will be smarter with the amount of knowledge they have